2014
DOI: 10.4103/1305-7456.126241
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different irrigation systems on smear layer removal: A scanning electron microscopic study

Abstract: Objectives:To evaluate effectiveness of the apical negative pressure irrigation (EndoVac), passive ultrasonic irrigation (PUI), and conventional needle irrigation (CI) systems on smear layer (SR) removal.Materials and Methods:Sixty single-rooted canines were prepared using NiTi rotary files and subjected to different irrigation regimens: EndoVac with NaOCl (Group 1) or NaOCl/EDTA (Group 2); PUI with NaOCl (Group 3) or NaOCl/EDTA (Group 4); CI with NaOCl (Group 5) or NaOCl/EDTA (Group 6). The roots were split l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
(37 reference statements)
3
15
1
3
Order By: Relevance
“…Clinically, removal of the resultant SL from canal shaping is necessary as it might harbor packed microbes and infected debris in the canal wall 40,41) . The SI was unable to clean the root canal system effectively, which is consistent to past studies 15,37,42) . The EV achieved the best results in terms of SL removal.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Clinically, removal of the resultant SL from canal shaping is necessary as it might harbor packed microbes and infected debris in the canal wall 40,41) . The SI was unable to clean the root canal system effectively, which is consistent to past studies 15,37,42) . The EV achieved the best results in terms of SL removal.…”
Section: Discussionsupporting
confidence: 78%
“…However, it failed to completely clean all specimens. Ahmetoglu et al 42) reported the same finding. This might be attributed to the sole effect of the chemical means on the SL with short irrigation contact time.…”
Section: Discussionsupporting
confidence: 76%
“…Ahmetoglu et al . () evaluated the effectiveness of the apical negative pressure irrigation (EndoVac), passive ultrasonic irrigation (PUI), and conventional needle irrigation (CI) systems on the smear layer. They reported that no matter which irrigation system was used, the use of NaOCl alone failed to remove the smear layer and in the NaOCl/EDTA combination groups, the smear layer was removed partially or completely.…”
Section: Discussionmentioning
confidence: 99%
“…The concussion of ultrasonic tips in the root canal can produce the cavitation effect, micro acoustic streaming effect, and synergistic effect [7]. Compared to traditional syringe irrigation, ultrasonic irrigation can enhance the washing solution's ability to dissolve and disinfect the organic matter; remove large amounts of infectious microbial and debris in the smear layer of main root canal, canal collateral, curved canal and/or isthmus [8]; open dentinal tubules; and reduce the chance of leaking debris and fluid mixtures through the apical foramen due to irrigation. Thus, this method is useful in dredging the thinned root canal in elderly patients and can improve the effect of collateral filling.…”
Section: Discussionmentioning
confidence: 99%